INTEGRATING LEARNING THEORIES, TEACHING METHODS, AND EDUCATIONAL ASSESSMENT ACROSS LANGUAGE, MATHEMATICS, AND LEGAL AWARENESS IN ELEMENTARY EDUCATION - Akhirur Rhomadon Matondang; Riswan Saleh; Hamka (PT. Jurnal Center Indonesia Publisher, 2026)
Elementary education requires coherent integration of learning theories, subject-specific teaching methods, and sound assessment practices to support students’ holistic development. This study aims to examine the implementation of learning theories and instructional methods across multiple subject areas, including basic legal awareness, listening skills in language learning, mathematics learning methodology, elementary school mathematics, educational assessment, and educational evaluation. The research employed a descriptive qualitative approach and was conducted at SD Negeri No. 101390 Batang Pane-I, Desa Batang Pane-I. Data were collected through classroom observations, semi-structured interviews with teachers, and documentation analysis. The findings indicate that student-centered and contextual teaching methods grounded in constructivist learning theory enhance student engagement and conceptual understanding across subjects. Moreover, formative assessment and reflective evaluation practices play a crucial role in improving instructional quality and learning outcomes. The study highlights the importance of integrating pedagogical theory, subject methodology, and assessment as a unified framework for effective elementary education.